Primary prevention of cardiovascular disease events with renin-angiotensin system blockade in autosomal dominant polycystic kidney disease dialysis patients: A nationwide cohort study. Issue 26 (2nd July 2021) - Lu, Chien-Lin; Lin, Chien-Yu; Lin, Lian-Yu; Chen, Pau-Chung; Zheng, Cai-Mei; Lu, Kuo-Cheng; Yeih, Dong-Feng
Abstract : Abstract: Although renin-angiotensin system (RAS) blockade has been shown to reduce cardiovascular disease (CVD) in the general population and high-risk subjects, their protective effect in autosomal dominant polycystic kidney disease (ADPKD) patients under dialysis was still unknown. By using the database from 1995 to 2008 Taiwan National Health Insurance Research Database (Registry for Catastrophic Illnesses), we included 387 ADPKD patients who received dialysis therapy, aged ≥ 18 year-old, and with no evidence of CVD events in 1997 and 1998. We utilized Cox proportional hazards regression analysis and propensity score matching to evaluate adjusted hazard ratios for all-cause mortality and CVD events in users (n=231) and nonusers (n = 156) of an angiotensin-converting enzymes inhibitor (ACEI) / angiotensin II receptor blocker (ARB) during the 12 years of follow-up. All study subjects were followed up for more than 3 months. There was no significant difference between the ACEI/ARB treatment group and the control group in incident CVD events except ischemic stroke and transient ischemic accident (TIA). The results remain similar between groups before and after propensity score matching. Moreover, there was no significant difference in outcomes between ACEI/ARB treatment over 50% of follow-up period and without ACEI/ARB treatment after propensity score matching. This nationwide cohort study failed to prove the protective effects of long-term ACEI or ARB on incident CVD events among APKD dialysis patients. Further larger scale, multicenter and randomized control trials are warranted to show the causal association